L'interaction des techniques de rédaction et des techniques d'interprétation des lois - Bisson, Alain-François (Les Cahiers de droit)

(untitled) (Faculté de droit de l’Université Laval, 1980)
That there is an interaction effect between legislative drafting techniques and judicial methods for the interpretation of statutes is beyond question. But what really lies behind that interaction is a sort of tug of war between two opponents, legislator and judge, each obsessed with the other and each driven by the other to dig in his heels and resist at all costs, regardless of the caricature they may make of their respective roles. The presumed hostility of judges to the labours of the legislator leads to petty drafting techniques which, in turn, leave judges with a feeling of the legislator's hostility towards them, thus resulting in interpretation techniques which, if not altogether negative, clearly indicate the judges' distrust of the legislator. This vicious circle must be broken and a return made to broader conceptions of legal interpretation. The judges, no doubt, have their part to play in the task of reconciliation. But no real progress can be made if the legislator does not first set the proper example in taking the honourable and calculated risk of expressing himself in simple and open language. The recent change in drafting techniques, at least in certain classes of statutes, is an encouraging sign in that regard.